Current state of abdominal wall transplantation. Issue 2 (April 2016) - Giele, Henk; Vaidya, Anil; Reddy, Srikanth; Vrakas, Giorgios; Friend, Peter
Abstract : Purpose of review: Primary closure of the abdominal wall remains one of the early challenges of intestinal transplantation. Our aim is to review the role of abdominal wall transplantation in achieving tension-free closure of the abdomen. Recent findings: In total, 38 full-thickness vascularized abdominal wall transplants, six partial-thickness vascularized and 17 partial-thickness nonvascularized rectus facia grafts have been reported worldwide. Different techniques have been described. The most popular choice seems to be the full-thickness vascularized abdominal wall allograft, where the anastomosis is performed either in a micro- or macrovascular fashion. Temporary 'remote' revascularisation of the allograft has been performed in some cases onto the recipient's forearm vessels when there is a long anticipated cold ischaemia time (>5 h). Preliminary data suggest that the abdominal wall skin rejection might be an early predictor of intestinal rejection. Vascularized and nonvascularized rectus fascia may be effective when there is inadequate healthy muscle/fascia but sufficient skin cover. Summary: Several centres have already proved the technical and immunologic feasibility of partial or full-thickness abdominal wall transplantation. It is an effective option to achieve primary abdominal closure following intestinal transplantation and in its full-thickness form, it may be useful for monitoring rejection in visceral organs.